2021
DOI: 10.1111/sjop.12766
|View full text |Cite
|
Sign up to set email alerts
|

First‐person access to decision‐making using micro‐phenomenological self‐inquiry

Abstract: Micro‐phenomenology is a method for improving first‐person reports of experience. Usually, micro‐phenomenology is conducted using a second‐person interviewer who guides someone investigating an experience. This has the advantage that the interviews can be done with untrained subjects. However, it is possible to perform micro‐phenomenological self‐inquiry, a form of self‐interview technique, without a second‐person interviewer. This has several advantages, such as being more time and cost effective. Questionabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…A typical example of this is a study done by Nisbett and Wilson ( Nisbett and Wilson, 1977 ), which showed that we often make mistakes when we investigate our own decision making process, and the criticism of introspection continues today ( Schwitzgebel, 2008 ; Smithies, 2013 ). Some research exists, showing that introspection may become more reliable when it is done methodologically through for instance micro-phenomenology ( Petitmengin et al, 2013 ; Sparby et al, 2021 ), Although micro-phenomenology is mostly conducted by guiding others to investigate their experience systematically, it may also be done in a way where a person investigates their own experience ( Sparby et al, 2020b ; Sparby, 2023 ) and methodical advancements like relying on a cultivation of the sense of certainty may improve the reliability of reports ( Sparby et al, 2020a ). Still, the empirical evidence that it is possible to improve the reliability of reports is scarce.…”
Section: The Theory Practice and Challenges Of Introspective Research...mentioning
confidence: 99%
“…A typical example of this is a study done by Nisbett and Wilson ( Nisbett and Wilson, 1977 ), which showed that we often make mistakes when we investigate our own decision making process, and the criticism of introspection continues today ( Schwitzgebel, 2008 ; Smithies, 2013 ). Some research exists, showing that introspection may become more reliable when it is done methodologically through for instance micro-phenomenology ( Petitmengin et al, 2013 ; Sparby et al, 2021 ), Although micro-phenomenology is mostly conducted by guiding others to investigate their experience systematically, it may also be done in a way where a person investigates their own experience ( Sparby et al, 2020b ; Sparby, 2023 ) and methodical advancements like relying on a cultivation of the sense of certainty may improve the reliability of reports ( Sparby et al, 2020a ). Still, the empirical evidence that it is possible to improve the reliability of reports is scarce.…”
Section: The Theory Practice and Challenges Of Introspective Research...mentioning
confidence: 99%